Maternity Hospital San Bartolomé. Recap of its Beginnings - Bonilla, Zoila (1996)
Start timing of a hospital appointment with Father Pedro Poveda is appropriate when the reference is on St. Bartholomew's Hospital, as its founder and spiritual father Fray Bartolome de Vadillo gave his work a timeless impulse based on the most significant act human love, that is, to help the needy.